CD27 natural killer cell subsets play different roles during the pre-onset stage of experimental autoimmune encephalomyelitis. Issue 6 (August 2016) - Gao, Ming; Yang, Yan; Li, Daling; Ming, Bingxia; Chen, Huoying; Sun, Yan; Xiao, Yifan; Lai, Lin; Zou, Huijuan; Xu, Yong; Xiong, Ping; Tan, Zheng; et al.
NK cells participate in the development of human multiple sclerosis (MS) and mouse experimental autoimmune encephalomyelitis (EAE), but the roles of different NK cell subsets in disease onset remain poorly understood. In this study, murine NK cells were divided into CD27 high and CD27 low/− subsets. The CD27 high subset was decreased and the CD27 low/− subset was increased in lymphoid organs during the pre-onset stage of EAE. Compared with the counterpart in naïve mice, the CD27 high subset showed lower expression of Ly49D, Ly49H and NKG2D, and less production of IFN-γ, whereas the CD27 low/− subset showed similar expression of the above mentioned surface receptors but higher cytotoxic activity in EAE mice. Compared with the CD27 high subset, the CD27 low/− subset exhibited increased promotion of DC maturation and no significant inhibition of T cells proliferation and Th17 cells differentiation in vitro . Additionally, adoptive transfer of the CD27 low/− subset, but not the CD27 high subset, exacerbated the severity of EAE. Collectively, our data suggest the CD27 NK cell subsets play different roles in controlling EAE onset, which provide a new understanding for the regulation of NK cell subsets in early autoimmune disease.